Opportunistic Computed Tomography and Spine Surgery: A Narrative Review. Issue 7 (October 2020) - Shirley, Matthew; Wanderman, Nathan; Keaveny, Tony; Anderson, Paul; Freedman, Brett A.
Study Design: Narrative review. Objective: This article seeks to provide a narrative review regarding the ability of opportunistic information available from computed tomography (CT) scans to guide decisions in spine surgery related to patient bone quality. Methods: A review of the literature (limited to human and English language) was performed via PubMed and Google Scholar using the search terms; "osteoporosis" AND "opportunistic" AND "computed tomography" AND "spine surgery." The titles and then abstracts of all identified citations were reviewed for inclusion by 2 of the authors (MS, BAF). Relevant articles were then studied in full text. Results: A review of the literature found 25 articles that were selected for inclusion in this narrative review. These articles were broadly divided into 4 subcategories: (1) opportunistic CT (oCT) and osteoporosis detection, (2) oCT data and the quality of screw fixation, (3) utilization of Hounsfield units to assess clinical and/or radiographic outcomes following spine fusion, and (4) virtual stress testing in spine surgery. Conclusion: The literature on oCT, as well as associated virtual stress-testing techniques, demonstrate the potential to enhance spine surgery outcomes by preoperatively identifying at-risk patients in need of bone health optimization and informing best techniques for performing spinal fusion surgery on patients with diminished bone quality. While our narrative summary of the limited literature to date suggests a promising future for oCT data, significant additional research and/or radiographic workflow standardization is needed to validate these methods for clinical use.